Developing Personal Potential Through Self-Leadership and Servant Leadership for Youth of the HKI Pulo Jaba Parmaksian Porse Toba Church - Anakampun, Martulus; Amelia, Intan; Togatorop, Debora; Waruwu, Herliana; Berutu, Janwardi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This service explores the role of self-leadership and servant leadership in developing the self-potential of teenagers at the Indonesian Huria Kristen Church (HKI) Pulo Jaba Parmaksian, Porse Toba. Using a qualitative method with a case study approach, data was collected from 30 teenagers active in the coaching program, with in-depth interviews conducted with 10 teenagers involved in leadership and service activities in the church. The results show that the coaching program is significant in developing self-leadership skills and understanding of servant leadership in adolescents, with the support of church leaders and mentors being key factors in the success of the program. Despite obstacles such as limited resources, youth enthusiasm and church support provided the impetus for further development. This research confirms the importance of integrating these two leadership approaches in developing church youth.